Pengaruh Pembelajaran Kontekstual Berbasis Outing Class Terhadap Pembendaharaan Kosa Kata Bahasa Indonesia Siswa SD Inpres Minasa Upa 1 - Asrul; Haslinda; Desy Ayu Andhira (Journal of Cultural Relativism (JCR), 2024)
This research aims to determine the effect of Outing Class-based contextual learning on the Indonesian vocabulary of class IV SD Inpres Minasa Upa 1, and to determine the effect of Outing Class-based contextual learning on the Indonesian vocabulary of class IV SD Inpres Minasa Upa 1. This research approach is an approach quantitative with a Pre-Experimental research design in the form of OneGroupPretest-Posttest research. The population of this research was fourth grade students at SD Inpres Minasa Upa 1. The sampling technique used was a saturated sample technique, by making the population as a sample, namely 24 students. The research instruments used were learning outcomes tests and observation sheets. while the data collection techniques in this research use observation and tests. The data analysis used is descriptive data analysis and inferential data analysis. The results of this research show that the results of the Paired Sample T-Test at a significance level of 5% obtained a significant value (2-tailed) <α (0.00 < 0.05) or t count > t table (8.816 > 2.086). Based on these results, it can be concluded that the influence of Outing Class-based contextual learning has an influence on the vocabulary of class IV students at SD Inpres Minasa Upa 1, Rappocini District, Makassar City, South Sulawesi.